PERLINDUNGAN HUKUM BAGI DRIVER OJEK ONLINE TERHADAP PEMBATALAN SEPIHAK OLEH KONSUMEN YANG TIDAK BERITIKAD BAIK - Sinthiarahma Felyna Megawati; Amad Sudiro (Jurnal Hukum Adigama, 2020)
Legal protection seeks to provide protection to parties whose rights and obligations have been harmed. The use of application-based online transportation is very much needed, the presence of Gojek with various services, one of which is Go-Food. Food delivery service for consumers. In its implementation, consumers who do not have good intentions occur when the food has been paid for. How is the legal protection for online motorcycle taxi drivers against unilateral cancellation by consumers who do not have good intentions based on law number 8 of 1999 concerning consumer protection? The author uses normative legal research methods and uses interview data as a support. The results of the study reveal that as drivers who experience losses due to the cancellation are entitled to legal protection and PT Gojek Indonesia as the application provider is also responsible for these losses even though the contents of the agreement have a transfer of responsibility. As a result, it is not clear which party can be responsible for the losses suffered by drivers. The explanation should have known the severe responsibility of the parties, which is clearly regulated in the partnership agreement between PT Gojek Indonesia and the driver which was made with mutual consent regarding the forms of responsibility and legal protection that drivers get.